If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + i)(i + 2) = 0 Reorder the terms: (1 + i)(2 + i) = 0 Multiply (1 + i) * (2 + i) (1(2 + i) + i(2 + i)) = 0 ((2 * 1 + i * 1) + i(2 + i)) = 0 ((2 + 1i) + i(2 + i)) = 0 (2 + 1i + (2 * i + i * i)) = 0 (2 + 1i + (2i + i2)) = 0 Combine like terms: 1i + 2i = 3i (2 + 3i + i2) = 0 Solving 2 + 3i + i2 = 0 Solving for variable 'i'. Factor a trinomial. (2 + i)(1 + i) = 0Subproblem 1
Set the factor '(2 + i)' equal to zero and attempt to solve: Simplifying 2 + i = 0 Solving 2 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + i = 0 + -2 i = 0 + -2 Combine like terms: 0 + -2 = -2 i = -2 Simplifying i = -2Subproblem 2
Set the factor '(1 + i)' equal to zero and attempt to solve: Simplifying 1 + i = 0 Solving 1 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + i = 0 + -1 i = 0 + -1 Combine like terms: 0 + -1 = -1 i = -1 Simplifying i = -1Solution
i = {-2, -1}
| 4+3a=25 | | 8n-12=-12+8 | | 19=7x+y | | 10-2x=-5x+13 | | 3y=-x-8 | | 35=x(x-2) | | -5x+3y=-9 | | 6x^2-11x=35 | | 2y-x=-5 | | Y=2x^4-3x^3-15x^2+32x-12 | | 7mn-3n= | | 17x+12=29 | | pq-3p= | | 5y-yz= | | 20x^2-17x=63 | | 0.3x-0.1(1-4x)=-0.5(x-7) | | 2x^2+19x+42=0 | | 4-m=20 | | 0.1f-6.5=1.6f-2 | | 5w+1=9 | | 6=-8+n/4 | | 3x^2-4x=-2 | | 3-2d=4(2d-7) | | 0.02(50)+0.07t=0.04(25+t) | | 7r-17=-26+4r | | 25=-50n | | 4s-16=-24+8s | | 25=-50 | | 6+5n=-4 | | 60= | | -4+13=13x-3-12x | | 3x^2+x=-7 |